The relationship Customer Knowledge Management and Customer Relationship Management with improving organizational performance - Taghi Sahraei, Mohammad; Eskandarpour, Behrouz (Revista de la Universidad del Zulia, 2019)
This study was conducted with aim to investigate the relationship between Customer Knowledge Management (CKM) with Customer Relationship Management (CRM) and Improve organizational performance in the Mehr Eqtesad Bank of Ardabil Province in 2015. the statistical community consists of Ardebil province Mehr Eqtesad Bank employee, statistical sample were obtained 133 persons according to Cochran formula. Sampling method was stratified random. Research method is correlation descriptive that was conducted in cross-sectional form. The data collect tools were standard questionnaires to examine questionnaire validity, and to examine questionnaire reliability, Cranach’s alpha in software SPSS were used. Before testing the hypothesis Data normality was confirmed by using Kolmogorov-Smirnov tests. Results showed that data research was normal. To test the hypothesis one to three the Pearson correlation and linear multivariate regression method were used. Those results showed significant relationship between CKM with CRM and Improve organizational performance also there was significant relationship between CRM and Improve organizational performance.